2013
DOI: 10.1016/j.immuni.2013.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Histone Methyltransferase Ash1l Suppresses Interleukin-6 Production and Inflammatory Autoimmune Diseases by Inducing the Ubiquitin-Editing Enzyme A20

Abstract: Histone modifications play important roles in multiple physiological processes by regulating gene expression. However, the roles of histone modifications in immunity remain poorly understood. Here we report that Ash1l, a H3K4 methyltransferase, suppressed interleukin-6 (IL-6), and tumor necrosis factor (TNF) production in Toll-like receptor (TLR)-triggered macrophages, protecting mice from sepsis. Ash1l-silenced mice were more susceptible to autoimmune disease as a result of enhanced IL-6 production. Ash1l enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
107
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 43 publications
5
107
0
Order By: Relevance
“…77 In addition, histone methyltransferase Ash1l binds to the promoter regions of A20 gene to enhance the H3K4 methylation level, thus inducing A20 gene transcription and expression, consequently suppressing TLR signaling and inflammatory autoimmune diseases. 78 These studies further highlight the importance of crosstalk between PTM and chromatin modification in innate immune signaling regulation.…”
Section: Molecular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 87%
“…77 In addition, histone methyltransferase Ash1l binds to the promoter regions of A20 gene to enhance the H3K4 methylation level, thus inducing A20 gene transcription and expression, consequently suppressing TLR signaling and inflammatory autoimmune diseases. 78 These studies further highlight the importance of crosstalk between PTM and chromatin modification in innate immune signaling regulation.…”
Section: Molecular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 87%
“…Many molecules have been found to negatively regulate TLR signalling, ranging from extracellular decoy receptors to intracellular inhibitors 12 . In a recent study, histone methyltransferase Ash1l was found to suppress TLR-triggered inflammatory cytokine production and Ash1l-silenced mice were more susceptible to autoimmune disease 13 . Although intensively studied, the mechanisms by which TLR signal transduction is activated and regulated have not yet been fully understood.…”
mentioning
confidence: 97%
“…Ezh2 also was found to specifically enhance Th cell differentiation and plasticity via transcriptional regulation of other lineage-specifying genes (17). Ashl1, a histone H3 lysine 4 methyltransferase, could induce A20 expression to suppress IL-6 production in inflammatory autoimmune diseases (18). However, the precise roles and the underlying mechanisms of the epigenetic molecules in the regulation of the inflammatory innate response remain to be fully investigated.…”
mentioning
confidence: 99%